Foundation failure & repair - Marshall, Duncan; Brown, Stephen; University of the West of England, Bristol. Faculty of the Built Environment (Bristol : Faculty of the Built Environment, University of the West of England, 2007)
This new film includes a brief history of domestic foundations and explains the main causes of foundation failure. The film covers problems of settlement, subsidence, heave, landslip, flooding and earthquakes. The second part of the film describes the process of recording, monitoring and diagnsis and illustrates a number of repairs options
Title from title screen
Keywords: Foundations